MANAJEMEN SANTRI DI PONDOK PESANTREN MUSTHAFAWIYAH PURBABARU KECAMATAN LEMBAH SORIK MARAPI KABUPATEN MANDAILING NATAL - Mahdi Akbar Rambe; Zulhamri Zulhamri (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2022)
Management is the process of utilizing organizational resources to achieve organizational goals. Improving management is one of the efforts to improve the quality of education. This study aims to find out how the acceptance of new students, coaching and development of students, recording and reporting as well as graduation and alumni of Pondok Pesantren Musthafawiyah Purbabaru. The research method uses qualitative research. Data obtained from the results of observations, interviews and documents. Data processing techniques through reduction, data presentation and drawing conclusions. The results of the research on the acceptance of new students are that it provides equal opportunities for every prospective new student to register. The announcement contains the terms of registration, time and place of registration. Each prospective student may go directly to the second or third grade on the condition that a test is carried out. Guidance and development of students through classroom learning, worship routines such as congregational prayers, sunnah fasting Monday-Thursday and the Koran, through student councils, student unions and banjars by studying speeches, muzakarah independently. Recording and reporting through the main book, records of violations and student achievements. Students' graduation is carried out after students take the final exam for class VII. After graduation, every alumni of the Musthafawiyah Purbabaru Islamic Boarding School joins the Musthafawiyah Abituren Corps (KAMUS) in every district and city branch.